2015
DOI: 10.1371/journal.ppat.1004778
|View full text |Cite
|
Sign up to set email alerts
|

Immune Antibodies and Helminth Products Drive CXCR2-Dependent Macrophage-Myofibroblast Crosstalk to Promote Intestinal Repair

Abstract: Helminth parasites can cause considerable damage when migrating through host tissues, thus making rapid tissue repair imperative to prevent bleeding and bacterial dissemination particularly during enteric infection. However, how protective type 2 responses targeted against these tissue-disruptive multicellular parasites might contribute to homeostatic wound healing in the intestine has remained unclear. Here, we observed that mice lacking antibodies (Aid-/-) or activating Fc receptors (Fcrg-/-) displayed impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…Neutrophils, readily identified by the expression of MPO, are the predominant CXCR2+ cells among blood leukocytes, and CXCR2 is a key regulator of their recruitment and effecting responses3. In conjunction with the observation of the increased circulating concentration of CXCL1, it is highly likely that the CXCL1-CXCR2 axis was involved in the focal accumulations of neutrophils that were found in IPAF lungs here and in other reports8202122232425.…”
Section: Discussionsupporting
confidence: 60%
“…Neutrophils, readily identified by the expression of MPO, are the predominant CXCR2+ cells among blood leukocytes, and CXCR2 is a key regulator of their recruitment and effecting responses3. In conjunction with the observation of the increased circulating concentration of CXCL1, it is highly likely that the CXCL1-CXCR2 axis was involved in the focal accumulations of neutrophils that were found in IPAF lungs here and in other reports8202122232425.…”
Section: Discussionsupporting
confidence: 60%
“…Hoeksema et al showed that Trichuris suis soluble products evoke an M2-type macrophage via epigenetic changes (42). Also, macrophages cotreated with Ascaris suum E/S products and immune serum displayed enhanced wound-healing activity in an in vitro model (62). Thus, we speculate that monocytes recruited into the peritoneal cavity are converted into immunoregulatory monocyte-like cells by exposure to the HdAg and/or released host factors, and that these cells represent another mechanism by which HdAg treatment could ameliorate colitis.…”
Section: Discussionmentioning
confidence: 99%
“…154,191 Recovery from Heligmosomoides polygyrus induced intestinal pathology also involves m producing chemokine ligands for CXCR2 on fibroblasts, driven in part via CD64. 192 The ability of m to induce IL-22 production by ILC3 also favours restitution of a damaged epithelial barrier, 80,193 while TGF R mediated suppression of IL-33 production by m has been proposed to mediate resolution of chemical colitis. 190 Arginase produced by alternatively activated m in parasite infections is a further important tissue repair mechanism under these conditions.…”
Section: Macrophages In Intestinal Inflammationmentioning
confidence: 99%